2013
DOI: 10.12688/f1000research.2-153.v1
|View full text |Cite
|
Sign up to set email alerts
|

Reporting research antibody use: how to increase experimental reproducibility

Abstract: Research antibodies are used in a wide range of bioscience disciplines, yet it is common to hear dissatisfaction amongst researchers with respect to their quality. Although blame is often attributed to the manufacturers, scientists are not doing all they can to help themselves. One example of this is in the reporting of research antibody use. Publications routinely lack key details, including the host species, code number and even the company who supplied the antibody. Authors also fail to demonstrate that val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…There have been calls to standardize antibody production, characterization and use [ 24 , 25 ]. It is recommended that journals insist that authors be more transparent and consistent with reporting antibody details [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been calls to standardize antibody production, characterization and use [ 24 , 25 ]. It is recommended that journals insist that authors be more transparent and consistent with reporting antibody details [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of antibodies across cancer biology—from basic research to diagnostics to therapeutics—is pervasive (13, 30). While standards have been applied, formally or informally, to the generation and use of diagnostic and therapeutic antibodies, basic research antibody reagents are generally devoid of any kind of consistency or standardization.…”
Section: Lack Of Standards In Basic Biological Researchmentioning
confidence: 99%
“…While standards have been applied, formally or informally, to the generation and use of diagnostic and therapeutic antibodies, basic research antibody reagents are generally devoid of any kind of consistency or standardization. Although blame is often pointed at the manufacturers, Helsby et al(30) contend that scientists and publishers are not doing everything they can to improve the situation and thus improve reproducibility, such as failing to provide thorough reporting of research antibody use or demonstrating that antibodies were validated. Moreover, publications routinely do not provide the host species, code number, and even the antibody supplier.…”
Section: Lack Of Standards In Basic Biological Researchmentioning
confidence: 99%
“…Simply put, suppliers cannot possibly generate all information by themselves, especially since an antibody is typically used for different applications and tissues. Furthermore, it was suggested that journals should add antibody reporting guidelines, instructing authors to include antibody reports 7 . The antibody search engine and review database pAbmAbs, ( http://pabmabs.com/wordpress/ ) presented by founder Dr Simon Glerup, also provides a useful platform for researchers to share antibody reports.…”
Section: Independent Antibody Validationmentioning
confidence: 99%